Fundamentals of nursing : the art and science of nursing care - 4 0 16; CSFN. Taylor, Carol; 5 (Philadelphia, Pennsylvania : Lippincott Williams & Wilkins, 2008)
A comprehensive textbook for beginning nursing students that takes a holistic approach and includes a CD-ROM containing video demonstrations of skills and interactive activities and case studies.
Introduction to nursing -- Health of the individual, family, and community -- Cultural diversity -- Health illness -- Theory, research, and evidence-based practice -- Values, ethics, and advocacy -- Legal implications of nursing -- Healthcare delivery systems -- Continuity of care -- Home healthcare -- Blended skills and critical thinking throughout the nursing process -- Assessing -- Diagnosing -- Outcome identification and planning -- Implementing -- Evaluating -- Documenting, reporting, and conferring -- Developmental concepts -- Conception through young adult -- The aging adult -- Communicator -- Teacher and counselor -- Leader and manager -- Vital signs -- Health assessment -- Safety, security, and emergency preparedness -- Asepsis and infection control -- Complementary and alternative therapies -- Medications -- Perioperative nursing -- Self-concept -- Stress and adaptation -- Loss, grief, and dying -- Sensory stimulation -- Sexuality -- Spirituality -- Hygiene -- Skin integrity and wound care -- Activity -- Rest and sleep -- Comfort -- Nutrition -- Urinary elimination -- Bowel Elimination -- Oxygenation -- Fluid, electrolyte, and acid-base balance.
Rev. ed. of: Fundamentals of nursing / Carol Taylor, Carol Lillis, Priscilla LeMone. 5th ed. c2005.
Includes bibliographical references and index.
Adult;Adult
Keywords: 2 -- 0; 6; Nursing.;Nursing Care.;Nursing Process.;Nursing.; 20; 2